Influence Of Halal Brand Image, Halal Brand Trust And Halal Brand Loyalty On Purchase Intention In Wardah Skincare Users - Sukmawati Sukmawati; S Larasati Ayu Sekarsari (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study aims to determine the effect of brand image, brand trust, and brand loyalty on purchase intention of Wardah products. Methodology: By using quantitative research with hypothesis testing, this study involved a sample of 156 respondents who used Wardah skincare products. Primary data for research was obtained through questionnaires. The analysis methods used include multiple linear regression, coefficient of determination (R²), coefficient of correlation and determination, t-test, F-test, and classical assumption tests, using WarpPLS 7.0 software. Results: The results of this study indicate that brand image, brand trust, and brand loyalty have a significant effect on the purchase intention of Wardah skincare products. In addition, brand image also has a considerable role in influencing the purchase intention of Wardah skincare products. However, perceived quality does not have a significant influence on the purchase intention of Wardah skincare products. Findings: The findings confirm that brand image, trust, and loyalty are key drivers of purchase intention, while perceived quality appears to be less influential in this specific context. Novelty & Originality: The novelty of this study lies in the simultaneous examination of brand image, brand trust, brand loyalty, and perceived quality within a single framework for a local halal cosmetic brand in Indonesia. Its originality emerges from the empirical testing of these variables in the context of Wardah products, a leading Indonesian halal skincare brand that has received limited academic scrutiny. Conclusions: The study concludes that strengthening brand image, trust, and loyalty is essential for enhancing consumer purchase intention, while perceived quality may not be a primary concern for this product category. Type of Paper: This paper is an empirical research paper.